Source memory for advertisements: The role of advertising message credibility. - Bell, Raoul; Mieth, Laura; Buchner, Axel (Memory & Cognition, 2021)
Advertising is seen as an untrustworthy source because of the perceived self-interest of the advertisers in presenting product information in a biased or misleading way. Regulations require advertising messages in print and online media to be labeled as advertisements to allow recipients to take source information into account when judging the credibility of the messages. To date, little is known about how these source tags are remembered. Research within the source-monitoring framework suggests that source attributions are not only based on veridical source memory but are often reconstructed through schematic guessing. In two experiments, we examined how the credibility of advertising messages affects these source attribution processes. The source of the messages affected judgments of credibility at the time of encoding, but the source tags were forgotten after a short period of time. Retrospective source attributions in the absence of memory for the source tags were strongly influenced by the a priori credibility of the messages: Statements with a low a priori credibility were more likely to be (mis)attributed to advertising than statements with high a priori credibility. These findings suggest that the mere labeling of untrustworthy sources is of limited use because source information is quickly forgotten and memory-based source attributions are strongly biased by schematic influences.